Aerobic training reduces oxidative stress in skeletal muscle of rats exposed to air pollution and supplemented with chromium picolinate - Bruna Marmett; Ramiro Barcos Nunes; Kellen Sábio de Souza; Pedro Dal Lago; Cláudia Ramos Rhoden (Taylor & Francis Group, 2018)
Objective: The purpose of this study was to investigate the effects of chromium picolinate (CrPic) supplementation associated with aerobic exercise using measures of oxidative stress in rats exposed to air pollution. Methods: Sixty-one male Wistar rats were divided into eight groups: residual oil fly ash (ROFA) exposure and sedentary (ROFA-SED); ROFA exposure, sedentary and supplemented (ROFA-SED-CrPic); ROFA exposure and trained (ROFA-AT); ROFA exposure, supplemented and trained (ROFA-AT-CrPic); sedentary (Sal-SED); sedentary and supplemented (Sal-SED-CrPic); trained (Sal-AT); and supplemented and trained (Sal-AT-CrPic). Rats exposed to ROFA (air pollution) received 50 µg of ROFA daily via intranasal instillation. Supplemented rats received CrPic (1 mg/kg/day) daily by oral gavage. Exercise training was performed on a rat treadmill (5×/week). Oxidative parameters were evaluated at the end of protocols. Results: Trained groups demonstrated lower gain of body mass (P < .001) and increased exercise tolerance (P < .0001). In the gastrocnemius, trained groups demonstrated increased SOD activity (P < .0001) and decrease levels of TBARS (P = .0014), although CAT activity did not differ among groups (P = .4487). Conclusion: Air pollution exposure did not lead to alterations in oxidative markers in lungs and heart, and exercise training was responsible for decreasing oxidative stress of the gastrocnemius.